Sumo of the opera - Nawrocki, Michael; Vischer, Phil.; Big Idea Productions ([Franklin, Tenn.] : Big Idea : Distributed by WordEntertainment, 2004)
Larry is a wrestler who somehow manages never to finish what he starts. Eventually his ability to take anything seriously lands him in the ring with Apollo Gourd. Will Larry hang in there to complete the match? How does a cucumber look in wrestling gear anyway? Find out in this lesson in perseverance where kids will learn that whenever you finish what you start, you come out a winner!
Voices: Mike Nawrocki, Phil Vischer.
MPAA rating: Not rated.
DVD, full screen (1.33:1) presentation; Dolby Digital.
Closed-captioned.
Keywords: Perseverance (Ethics) -- Juvenile drama; Wrestling -- Tournaments -- Juvenile drama; Cucumbers -- Juvenile drama; Feature films; Animated films; Children's films; Religious films; Video recordings for the hearing impaired